2022
DOI: 10.19109/ejpp.v9i1.11785
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of the Cambridge Lower Secondary English Curriculum: Teachers’ Voices at One Private School in Palembang

Abstract: The Cambridge curriculum is one of the international curricula. In Indonesia, Cambridge curriculum has been implemented, especially for teaching English. This study was aimed at finding out English teachers' perceptions toward the implementation of the Cambridge Lower Secondary English Curriculum at one private school in Palembang, Indonesia. A qualitative design with a case study was employed for this study. The data were gathered through in-depth interviews with two English teachers. Thematic analysis was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…This finding aligns with Kusumawati's (2019) research, which also utilized the "Super Minds" E-book as a teaching material. However, this is distinct from Holandyah's (2022) study, which identified the use of Cambridge Lower Secondary English materials supplemented by Internet sources. While both are Cambridge curriculum products, the Lower Secondary version is tailored for students aged 11-14 years.…”
Section: Discussionmentioning
confidence: 88%
“…This finding aligns with Kusumawati's (2019) research, which also utilized the "Super Minds" E-book as a teaching material. However, this is distinct from Holandyah's (2022) study, which identified the use of Cambridge Lower Secondary English materials supplemented by Internet sources. While both are Cambridge curriculum products, the Lower Secondary version is tailored for students aged 11-14 years.…”
Section: Discussionmentioning
confidence: 88%